2020
DOI: 10.9734/cjast/2020/v39i830591
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pre-mix Fungicide, Fluopyram and Trifloxystrobin 250SC against Purple Blotch Disease of Onion in Karnataka

Abstract: Onion (Allium cepa L.) also known as the bulb onion or is rightly called as Queen of kitchen. It is one of the oldest important vegetable crops grown in India. Among the various fungal diseases, purple blotch caused by Alternaria porri is one of the most serious disease of onion which causes extensive damage to bulbs as well as seed crop. Field experiment was carried out to know the effect of combi-fungicide Luna sensation 500SC (Fluopyram250SC and Trifloxystrobin 250SC) at 400, 500 and 600 ml /ha along with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The present studies were in fine tune with the findings of Ahmed et al (2017) who found that luna experience as an effective fungicide when applied at different intervals with regard to reducing purple blotch of onions as well as enhancing yield and growth of onion crops. Ravikumar et al (2020) also found that luna sensation 500 SC at 600 ml/ha proved to be superior in reducing onion purple blotch severity (22.03%) over rest of the treatments with enhanced bulb yield of 24.77 t/ha. The chemicals viz., fluopyram 17.7% + tebuconazole 17.7% SC and propiconazole EC @ 0.1 per cent proved to be best chemicals in managing the disease under field condition.…”
Section: Resultsmentioning
confidence: 84%
“…The present studies were in fine tune with the findings of Ahmed et al (2017) who found that luna experience as an effective fungicide when applied at different intervals with regard to reducing purple blotch of onions as well as enhancing yield and growth of onion crops. Ravikumar et al (2020) also found that luna sensation 500 SC at 600 ml/ha proved to be superior in reducing onion purple blotch severity (22.03%) over rest of the treatments with enhanced bulb yield of 24.77 t/ha. The chemicals viz., fluopyram 17.7% + tebuconazole 17.7% SC and propiconazole EC @ 0.1 per cent proved to be best chemicals in managing the disease under field condition.…”
Section: Resultsmentioning
confidence: 84%
“…This complexity underscores the critical need for sustainable disease management strategies that address the challenges posed by Alternaria porri in onion cultivation while mitigating environmental and health risks associated with traditional control methods. Management of this disease typically involves the application of fungicides like Mancozeb®, Floupyram®, Trifloxystrobin®, and Pyraclostrobin® (Mandi et al, 2020;Ravikumar et al, 2020;Paneru et al, 2020;Sarnobat et al, 2020). However, concerns over the environmental impact and risks to human health arise due to the continued use of such chemicals (Uddin et al, 2020;Haroon et al, 2020).…”
Section: Original Research Articlementioning
confidence: 99%
“…While conventional methods are helpful in disease escape and are much concerned with yield and growth indices, a combination of several traditional methods is considered a suitable integrated management practice to combat diseases. However, in the absence of genetic resistance in crops, crop production relies on the use of synthetic chemicals (Mandi et al, 2020;Ravikumar et al, 2020). Despite their effectiveness, synthetic chemicals have deleterious consequences on the environment, increase residual toxicity levels in produce, and tolerance among pathogens to fungicides (El-Mougy & Abdel-Kader, 2019; Kalsoom et al, 2019).…”
Section: Introductionmentioning
confidence: 99%